Reasons for resistance to change in nursing: an integrative review - Rozita Cheraghi; Hossein Ebrahimi; Nasrin Kheibar; Mohammad Hasan Sahebihagh (BMC, 2023)
Abstract Background Change is a very complex and multifaceted phenomenon that is intertwined with the understanding of nursing practice, so, resistance to change in nursing can be considered as an important challenge. Knowing the reasons for this resistance can help in solving it in nursing. Therefore, the present study was conducted with the aim of investigating the reasons for resistance to change in nursing as an integrated review. Methods This integrative review was conducted using the Whittemore & Knafl method in 5 stages, including problem identification, searching the literature, evaluating primary sources, analyzing data, and presenting the results. Databases like SID, Irandoc, Magiran, Google Scholar, Web of Science, PubMed, CINAHL, and Scopus were searched using the keywords; "Resistance", "Change", "Nursing", "Resistance to Change" and their Persian equivalents in the time range of 2000 to January 2023. After applying inclusion criteria and assessing the articles using Bowling's Quality Assessment Tool, finally, 15 papers were included from 2964. Results After reviewing and critically appraisal of the qualified articles, the findings were placed in three main categories including; (1) individual factors, (2) interpersonal factors, and (3) organizational factors and six subcategories. Conclusion Undoubtedly, change is an integral component in nursing care, and resistance to it is the result of a set of individual, interpersonal and organizational factors that change managers should pay special attention to in order to make changes due to the reasons of this resistance, and the development process of developing changes in the clinical field is easily possible.